K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

27 tháng 12 2023

1 . When I'm a child , my grandmother teachs me sing many folk songs.

2 . Local people in that village still follow the old lifestyle as thier ancestors

3 . He goes to bed late last night , therefore this morning he was feel tired

4 . Although , watching TV is not good way to relax , you shouldn't watch it too much

29 tháng 12 2023

1 When I was a child, my grandmother taught me to sing many folk songs

2 Local people in that village still follow the old lifestyle of their ancestors

3 He went to bed late last night therefore this morning he feels tired

4 Although watching TV is a good way to relax, you shouldn't watch it too much

AH
Akai Haruma
Giáo viên
28 tháng 12 2023

Lời giải:
a. Tứ giác $AMKN$ có 3 góc vuông $\widehat{A}=\widehat{M}=\widehat{N}=90^0$ nên $AMKN$ là hình chữ nhật.

b.

Xét tam giác $AEM$ và $AKM$ có:
$MA$ chung

$\widehat{AME}=\widehat{AMK}=90^0$
$EM=KM$ (do $E,K$ đối xứng nhau qua $M$)

$\Rightarrow \triangle AEM=\triangle AKM$ (c.g.c)

$\Rightarrow \widehat{EAM}=\widehat{KAM}(1)$

Tương tự:

$\triangle AKN=\triangle ADN$ (c.g.c)

$\Rightarrow \widehat{DAN}=\widehat{KAN}(2)$

Từ $(1); (2)\Rightarrow \widehat{EAM}+\widehat{MAN}+\widehat{DAN}=\widehat{KAM}+\widehat{MAN}+\widehat{KAN}=2\widehat{MAN}=2.90^0=180^0$

Hay $\widehat{EAD}=180^0$

$\Rightarrow E, A, D$ thẳng hàng.

AH
Akai Haruma
Giáo viên
28 tháng 12 2023

Hình vẽ:

26 tháng 12 2023

Từ đồng nghĩa với từ "local" có thể là:

 

1. Regional

2. Area

3. Community

4. Neighborhood

5. District

6. Provincial

7. Municipal

8. Indigenous

9. Domestic

10. Native

26 tháng 12 2023

Từ đồng nghĩa với từ "local" có thể là:

 

1. Regional

2. Area

3. Community

4. Neighborhood

5. District

6. Provincial

7. Municipal

8. Indigenous

9. Domestic

10. Native

27 tháng 12 2023

\(3x^2+2y^2=5xy\)

\(\Leftrightarrow3x^2+2y^2-5xy=0\)

\(\Leftrightarrow2\left(x^2-2xy+y^2\right)+x^2-xy=0\)

\(\Leftrightarrow2\left(x-y\right)^2+x\left(x-y\right)=0\)

\(\Leftrightarrow\left(x-y\right)\left[2\left(x-y\right)+x\right]=0\)

\(\Leftrightarrow\left(x-y\right)\left(3x-2y\right)=0\)

\(\Leftrightarrow3x-2y=0\Leftrightarrow x=\dfrac{2y}{3}\) Thay vào S

\(\Rightarrow S=\dfrac{y+\dfrac{4y}{3}}{y-\dfrac{4y}{3}}=-7\)

21 tháng 1 2024

Acid gì bạn